Investigate the Validity, Reliability and Standardization of Family Executive Function Scale among Married People - Javanbakht, Salman; Yousefi, Zahra (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to evaluate the validity and reliability of the Family Executive Performance Scale among married people over 18 years of age in Isfahan. Therefore, the research was of contextualization and instrumentation. Method: This research was a survey and instrument making. The statistical population of this study consisted of all married men and women over 18 years of age in Isfahan. The statistical sample consisted of 400 men and women who were selected by convenience sampling. The research instruments included the Executive Performance Scale (GIOA, Squid, Guy and Converdie, 2000) and the Spouse Emotional Experience Questionnaire (Ghafarollahi, Yousefi, 1399). Data were analyzed in two parts: descriptive (mean and standard deviation) and inferential (Pearson correlation, Cronbach’s alpha and exploratory factor analysis). Results: The results showed that internal consistency (α = 0.75), retest reliability (r = 0.450 and P <0.01) and coordination of questions were appropriate. The frequency distribution for the whole scale and its dimensions was close to the normal distribution. Since a higher score in family executive performance indicates poorer executive performance, the evidence of divergent validity with a scale of negative emotional experience (r = 0.576 and P <0.01) showed a positive and significant relationship with the spouse and the results Convergent validity showed a negative relationship between the total score of this scale and the positive emotional experience scale towards the spouse (r = -0.276 and P <0.01) and family performance (r = -0.711 and P <0.01). And there is a significant negative relationship between executive performance and family executive performance (r = -0.671 and P <0.01), which confirms concurrent validity. The results of exploratory factor analysis showed that this scale consists of eight factors, which are: family organization, family planning, family pursuit and perseverance, family emotional control, family working memory, family inhibition, family supervision and family initiation. Also, the correlation of each factor with the total score was significant, which all confirm the validity of the structure of this scale. Conclusion: According to these findings, it can be concluded that the executive performance scale has desirable psychometric properties and can be used in the field of education, research and counseling.